Making school reform work : new partnerships for real change - Hill, Paul T. (Paul Thomas), 1943-; Harvey, James, 1944- (Book collections on Project MUSE., 2004)
This text identifies roles for foundations and civic groups in defining strategies for big-city school reform and in ensuring that promised changes are implemented. The authors suggest the establishment of several independent institutions to support the reform of big-city schools.